The Dialectical Behavior Therapy Skills Worbook: Practical DBT Exercises for Learning Mindfulness, Interpersonal Effectiveness, Emotion Regulation - McKay, Matthew; Brantley, Jeffrey; Wood, Jeffrey C. (New Harbinger Publications, 2019)
The Dialectical Behavior Therapy Skills Workbook, a collaborative effort from three esteemed authors, offers straightforward, step-by-step exercises for learning these concepts and putting them to work for real and lasting change. Start by working on the introductory exercises and, after making progress, move on to the advanced-skills chapters. Whether you are a professional or a general reader, whether you use this book to support work done in therapy or as the basis for self-help, you'll benefit from this clear and practical guide to better managing your emotions.This book has been awarded The Association for Behavioral and Cognitive Therapies Self-Help Seal of Merit - an award bestowed on outstanding self-help books that are consistent with cognitive behavioral therapy (CBT) principles and that incorporate scientifically tested strategies for overcoming mental health difficulties. Used alone or in conjunction with therapy, our books offer powerful tools readers can use to jump-start changes in their lives. Find more help online at cbt-self-help-therapy.com. CBT Self-Help Therapy offers web-based treatment for borderline personality disorder (BPD) and emotion dysregulation based on the book The Dialectical Behavior Therapy Skills Workbook. This interactive program can be used by clients working on their own, or their therapists can monitor their work on the secure server. Other modules in CBT Self-Help Therapy offer treatment for stress, anxiety, depression, and anger.
Keywords: Conducta; Terapia; Trastornos Mentales